Insecticidal activity of isolated essential oils from three medicinal plants on the biological control agent, Habrobracon hebetor Say (Hymenoptera: Braconidae) - Asadi, Mohammad; Rafiee-Dastjerdi, Hooshang; Nouri-Ganbalani, Gadir; Naseri, Bahram; Hassanpour, Mahdi (Acta Biologica Szegediensis, 2019)
The effects of Allium sativum L. (Alliaceae), Piper nigrum L. (Piperaceae) and Glycyrrhiza glabra L. (Fabaceae) essential oils were investigated on the biological control agent, Habrobracon hebetor Say. The female wasps of H. hebetor were treated by LC30 concentrations of the tested essential oils for 24 h and their demography was investigated. Results indicated that the adult longevity, survival, fecundity, fertility, hatch rate, offspring sex ratio and the other demographic parameters negatively were affected by these essential oils. At the same time, our findings indicated that G. glabra essential oil has the less severe effect on H. hebetor. Accordingly, G. glabra essential oil seems to be a compatible botanical compound with H. hebetor for applying in integrated pest management programs.